Theoretical Framework (Module) for Short-Sea Shipping System Evaluation - Vytautas Paulauskas; Birutė Plačienė; Donatas Paulauskas; Rafał Koba; Patryk Lipka; Krzysztof Czaplewski; Adam Weintrit; Andrzej Chybicki (Applied Sciences)
Short-sea shipping, abbreviated SSS, is the transportation of goods by sea over relatively short distances, in contrast to intercontinental ocean and deep-sea shipping. Short-sea shipping (SSS) is important for cargo transportation in some regions of the world with many ports and well-developed liner shipping. The development and improvement of SSS systems is an important scientific and practical task. This article presents theoretical and experimental results of the development and optimization of SSS. A methodology for connecting and evaluating SSS and other transport chains was developed and tested by experimental studies, with the help of which it is possible to assess the efficiency of SSS and other transport chains, e.g., in terms of economy, freight transportation time, and environmental impact. The developed SSS methodology includes sea and land transport corridors, their assessment, and possible ways of optimizing transport chains using a comparative method and can be applied to various transport and logistics chains. The basis for the development and verification of the SSS methodology was the theoretical and experimental results of real short-sea shipping operations. The use of a comparative method based on which transport and logistics chains are assessed allows one to search for the most optimal SSS routes and possible factors that allow optimizing transportation costs and reducing transportation time and environmental impact.